Dewhurst's textbook of obstetrics & gynaecology - Edmonds, D. Keith; Dewhurst, John, Sir, 1920-2006 (Blackwell Pub., 2007)
This time honoured classic has been re-built completely: after six editions the editor has decided that a radical revision is necessary. The new edition has been developed as a result of intensive consultation with trainees in OB/GYN as to what they want, what they need and how they learn. The book is organised into two halves covering obstetrics and gynaecology. Within each, the chapters are structured into sections containing pedagogic features such as boxes, highlights and key points for the first time. It contains everything the clinician needs to practice the art of obstetrics and gynaeco.